Decoding the tuberculosis puzzle: mechanical factors driving disease progression - Cardona, Pere-Joan (Frontiers in Tuberculosis, 2025)
It is stated that, following infection with Mycobacterium tuberculosis (Mtb), only 5–10% of individuals will develop active tuberculosis (TB), predominantly in the pulmonary form. After excluding major comorbidities that impair immune responses—such as undernourishment, alcohol abuse, smoking, HIV infection, and diabetes—there remains no clear explanation for this progression. Extensive efforts have been made to identify a transcriptomic biosignature in blood to predict disease development, yet none have been successful. This perspective aims to provide insights into this phenomenon. In adults, pulmonary TB exhibits a particular tropism for the upper lobes, primarily due to localized mechanical factors. Reduced mobility exacerbates the neutrophilic inflammatory response fuelling Mtb extracellular growth, while gravitational stress impairs the function of secondary lobular septa, hampering lesion encapsulation. Interestingly, such tropism is absent in children, as these regional differences do not exist. Instead, they develop self-healing, small lesions known as Ghon foci. However, children have a significantly higher likelihood of developing disseminated extrapulmonary TB, a phenomenon that could be named as the pediatric TB paradox. This has traditionally been attributed to an immature immune response, but an alternative explanation may lie in the profound modifications occurring in lung parenchyma and microvascular maturation during the first 2 to 3 years of life. Ultimately, the evolution of Mtb suggests an original symbiotic relationship with humans, which has been disrupted by socio-demographic and cultural factors. These shifts may have transformed Mtb from a natural enhancer of Th1 responses and trained immunity into the leading infectious killer of humankind.